Speculative bubble on housing markets: Elements of an early warning system - Christian Dreger; Konstantin A. Kholodilin (DIW Economic Bulletin, 2011)
Excessive speculation on asset markets can cause significant macroeconomic losses in terms of production and employment. Such developments should be detected as early and as reliably as possible in order to enable corrective action through adequate economic policy measures. This is the goal of the early warning system, which was developed by DIW Berlin on behalf of the Federal Ministry of Finance for the housing market. The early warning system predicts price surges on real estate market that were caused by speculation. If speculative price developments are detected quickly, economic policy has enough leeway to find an adequate response and possibly prevent further development of the bubble.
Keywords: C25; C33; E32; E37; 330; house prices; early warning system; price bubbles